Keragaman Status Gizi dan Persentase Lemak Tubuh Mahasiswa Baru STIKes Baiturrahim - Arnati Wulansari; Kasyani Kasyani (Universitas Baiturrahim, 2021)
The role of nutrition in the life cycle is very important. If there is a problem with malnutrition, this is a sign that you are at risk of suffering from chronic disease. Measurement of nutritional status and body fat percentage is important as an initial screening to prevent the risk of chronic disease. This study aims to describe the performance of the nutritional status and body fat percentage of new student STIKes Baiturrahim 2020. This study used a cross-sectional study. The research was conducted at STIKes Baiturrahim Jambi in September 2019. The number of respondents was 148 people. The data used are the characteristics of the respondents (age, sex, body weight, and height) and the percent of body fat obtained from measurement of Bioelectrical Impedance Analysis (BIA). The results showed that most of them had normal nutritional status (64,2%) and body fat percentage was classified as normal (41,9%). It is recommended that students maintain normal nutritional status and body fat percentage and also always monitoring the body weight to prevent chronic disease